2018
DOI: 10.1007/s10659-018-9686-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Curvature in the Elastic Energy of Non-Euclidean Thin Bodies

Abstract: We prove a relation between the scaling h β of the elastic energies of shrinking non-Euclidean bodies S h of thickness h → 0, and the curvature along their mid-surface S. This extends and generalizes similar results for plates [BLS16, LRR] to any dimension and co-dimension. In particular, it proves that the natural scaling for non-Euclidean rods with smooth metric is h 4 , as claimed in [AAE + 12] using a formal asymptotic expansion. The proof involves calculating the Γ-limit for the elastic energies of small … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…In general, we expect that the type of limiting model does not only depend on α but also on other properties of the prestrain. Indeed, in a situation without homogenization it is shown in [8,36] that bending and von Karman type plate models arise in the case α = 0 depending on the geometry of the prestrain (see also [37] for related results in the case of rods and [31,32] for recent results for plates and shells beyond the von Karman regime). It is an interesting question if these results are stable with respect to (small) rapidly oscillating perturbations.…”
Section: Remarkmentioning
confidence: 98%
“…In general, we expect that the type of limiting model does not only depend on α but also on other properties of the prestrain. Indeed, in a situation without homogenization it is shown in [8,36] that bending and von Karman type plate models arise in the case α = 0 depending on the geometry of the prestrain (see also [37] for related results in the case of rods and [31,32] for recent results for plates and shells beyond the von Karman regime). It is an interesting question if these results are stable with respect to (small) rapidly oscillating perturbations.…”
Section: Remarkmentioning
confidence: 98%
“…Similar to the reasoning in [8], the proof of Theorem 1.2 relies on a corresponding Γ-convergence result where the notion of convergence of sequences of maps u h : B h (p) → M incorporates a blow-up which reveals the map f . One key additional difficulty for non-flat targets is that maps u h with small energy need not be continuous.…”
Section: X) and An Energymentioning
confidence: 98%
“…In [8] it is shown that the quadratic quantity I R(p) is actually induced by a scalar product and in particular I R(p) = 0 if and only if R(p) = 0. Recall that by Gauss' theorema egregium, a small ball B h (p) in M can be mapped into R n with zero energy E B h (p) if and only if R ≡ 0 on B h (p).…”
Section: X) and An Energymentioning
confidence: 99%
See 1 more Smart Citation
“…There is, by now, a considerable body of work on thin plates with pre-strain. We mention, with no attempt to be exhaustive, [12,24,25,28,29,38,39] and refer to our companion paper [11] for further discussion and references. As our primary interest is to model multilayers, our set-up is quite different from those of the aforementioned contributions where the pre-strain depends only on the in-plane variables.…”
Section: Introductionmentioning
confidence: 99%